2018
DOI: 10.11114/jets.v6i11.3533
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Presentation in Thai Secondary School ELT Coursebooks: An Analysis From Intercultural Perspectives

Abstract: Globalization has accelerated the growth of English and created a need for several changes in English language teaching (ELT), one of which is related to the role of ELT materials in facilitating interaction across cultures. Considering the fast growing importance of cultural content in ELT, this study explores issues of cultural presentation in Thai secondary school ELT coursebooks. The purpose of this study is twofold: first, to analyze cultural content presented in visuals and reading texts; second, to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…(Harpe, 2015). In this analysis, the statetements of attitudes were adapted from Thumvichit (2018) and the results were divided into five categories: 1) strongly disagree 2) disagree, 3) agree, 4) strongly agree.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Harpe, 2015). In this analysis, the statetements of attitudes were adapted from Thumvichit (2018) and the results were divided into five categories: 1) strongly disagree 2) disagree, 3) agree, 4) strongly agree.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the textbook review showed that teachers who used these five coursebooks, as well as future coursebook designers, must use pragmatics research and authentic examples to improve their lessons on request. In addition, the reserach of Thumvichit (2018) provided enrichment for analysis on the textbooks. Thumvichit, have not only analyzed cultural content presented in visuals and reading texts, but also investigated teacher's attitudes toward cultural presentation in ELT coursebooks.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Pornsakkul (2015) studied the teachers' opinions on the effectiveness of the textbook Smile 1 for grade 1 students, which he claimed to be the most popular in one of the southern provinces in Thailand, while Pinjinda (2015) conducted an intercultural analysis of three coursebook series (Books 1-6) used by grades 7-12, or Mattayomsuksa 1-6 Thai secondary school students. Thumvichit (2018) analyzed cultural content presented in visuals and reading texts from seven EFL textbooks for grade 7, or Mattayomsuksa 1, namely Bride 1, English in Mind 1, Messages 1, Motivate! 1, New World 1, Time Zone 1, and Your Space 1, and then investigated teachers' attitudes towards cultural presentation in these coursebooks.…”
Section: Introductionmentioning
confidence: 99%
“…Умение грамотно работать с информацией, и информационно-коммуникационная грамотность становятся важнейшим требованием подготовки как педагогов, так и учащихся [13; 14]. В современных условиях развития информационно-коммуникационных технологий и их повсеместного использования во всех сферах жизни сложно представить учебное издание, которое не предусматривает использования мультимедийных технологий, однако, важно следовать принципу информационно-коммуникативной оправданности [15][16][17]. Современное учебное издание должно быть, по возможности, мультимедийным, с заданиями, предусматриваю-щими использование ресурсов Интернета, но с учетом принципа опережающей компьютерной подготовки [18][19][20], особенно для студентов Института радиоэлектроники и информационных технологий.…”
Section: Introductionunclassified